İşyerinde psikolojik taciz: bir tıp fakültesi hastanesinde çalışan asistan doktor ve hemşirelerin algıları üzerine bir çalışma - Birik, Işıl (My University, 2009)
İŞYERİNDE PSİKOLOJİK TACİZ: BİR TIP FAKÜLTESİ HASTANESİNDE ÇALIŞAN ASİSTAN DOKTOR VE HEMŞİRELERİN ALGILARI ÜZERİNE BİR ÇALIŞMA İşyerinde psikolojik tacize ilişkin farkındalık düzeyini arttırmayı ve kavram yanılgılarını azaltmayı hedefleyen bu tez çalışmasında olgu detayları ile açıklanmış ve niteliksel ve niceliksel yöntemin birlikte kullanıldığı bir çalışma gerçekleştirilmiştir. Anket uygulamasını içeren ve 215 sağlık çalışanının katılımıyla gerçekleştirilen nicel araştırmada, işyerinde psikolojik tacize maruz kalma oranı farklı yöntemler kullanılarak tespit edilmiştir. ‘İşyeri Tacizi Ölçeği’nin kullanıldığı yöntemde katılımcıların %23.2’sinin, subjektif yöntemde ise %31.2’sinin psikolojik taciz mağduru olduğu saptanmıştır. Tanık olunan psikolojik taciz oranı ise %46.5 olarak gerçekleşmiştir. Katılımcıların en sık karşılaştığı psikolojik taciz davranışlarının; ‘işlerin yok yere bölünmesi’, ‘anlamsız görevler, yetiştirilemeyecek işler verilmesi’ ve ‘yersiz eleştiriler yapılması’ olduğu belirlenmiştir. Uzun süreli ve yukarıdan aşağıya doğru taciz, en sık karşılaşılan psikolojik taciz türleri arasında yer almıştır.

WORKPLACE BULLYING: A STUDY ON THE PERCEPTION OF DOCTORS AND NURSES IN A UNIVERSITY HOSPITAL This dissertation study which aimed to increase the awareness on the issue and decrease the erroneous perception of the concept, explores the ‘workplace bullying’ phenomenon in details and presents a cross-sectional study using both the qualitative and the quantitative method. The quantitative research included a cross-sectional questionnaire survey carried out among 215 healthcare professionals. In the survey, workplace bullying rates were determined with various methods; the ‘work harassment scale’ revealed that 23.2% of the participants were victims, whereas the same rate was determined as 31.2% in the subjective method and as 46.5% with regard to observations made by the participants. The most frequently encountered acts were ‘being unduly disrupted’ and ‘being given meaningless tasks’ and ‘being unduly criticized’. Long term and downward bullying were among the most frequently encountered types. The qualitative research explored the experiences of bullying among ten healthcare professionals who perceived themselves as victim and/ or witness. Data were collected using in-depth interviews. The examination of interviews revealed that the process of bullying starts with an environment of conflicting personal and organizational factors, followed by the increase in severity of negative acts which ends up with a situation in which the victim’s health is highly injured, whereas the colleagues and the organization is negatively effected and the victim is pushed to quit the job. This study emphasizes the importance of the personal or organizational active response to prevent or stop the problem, as well as the necessity for laws on the issue.
Keywords: Çalışma Psikolojisi; Psikolojik Taciz